PERANAN PARA PIHAK DALAM IMPLEMENTASI KEBIJAKAN PENGGUNAAN KAWASAN HUTAN UNTUK PERTAMBANGAN - Manifas Zubayr; Dudung Darusman; Bramasto Nugroho; Dodik Ridho Nurrochmat (Jurnal Analisis Kebijakan Kehutanan, 2014)
This study aimed to find the role and relationships among stakeholders in the policy implementation. Descriptive qualitative approach with indepth interview method, document and literature review and unstructured observations used in this study. Stakeholder analysis has been done by identifying the interests and influence of stakeholders, also an analysis of the rights, responsibility, revenues and relationship (4R's) of stakeholders. The study  results showed that there are nineteen stakeholders related to the policy implementation of the use of forest area. Ministry of Forestry is the main stakeholders while the leasehold of forest area license's holder become stakeholders' key in the policy implementation of the use of forest area. The role of both become a main factor of the successful implementation of policy. There is a good balance between the rights, responsibility and revenues for each stakeholder. While the relationships among stakeholders existed in various levels, from collaboration to conflict. Ministry of Forestry is expected to allocate deconcentration budget to implement the use of forest area policy. The regional government is also expected to prepare adequate human resources to conduct monitoring and evaluation activities such the leasehold of the forest area license.